The Impact of Caesarean Delivery on Paracetamol and Ketorolac Pharmacokinetics: A Paired Analysis. (20th May 2012) - Kulo, Aida; van Calsteren, Kristel; Verbesselt, Rene; Smits, Anne; Devlieger, Roland; de Hoon, Jan; Allegaert, Karel
Abstract : Pharmacokinetics is a first, but essential step to improve population-tailored postoperative analgesia, also after Caesarean delivery. We therefore aimed to quantify the impact of caesarean delivery on the pharmacokinetics of intravenous (iv) paracetamol (2 g, single dose) and iv ketorolac tromethamine (30 mg, single dose) in 2 cohorts eachof 8 women at caesarean delivery and to compare these findings with postpartum to quantify intrapatient changes. We documented a higher median paracetamol clearance at delivery when compared to 10–15 weeks postpartum (11.7 to 6.4 L/h·m 2, P < 0.01 ), even after correction for weight-related changes. Similar conclusions were drawn for ketorolac: median clearance was higher at delivery with a subsequent decrease (2.03 to 1.43 L/h·m 2, P < 0.05 ) in postpartum (17–23 weeks). These differences likely reflect pregnancy- and caesarean-delivery-related changes in drug disposition. Moreover, postpartum paracetamol clearance was significantly lower when compared to estimates published in healthy young volunteers (6.4  versus  9.6 L/h·m 2 ), while this was not the case for ketorolac (1.43  versus  1.48 L/h·m 2 ). This suggests that postpartum is another specific status in young women that merits focused, compound-specific pharmacokinetic evaluation.